Research advances in prevention and treatment of burn wound deepening in early stage - Lu, Meiqi; Zhao, Jie; Wang, Xiaochuan; Zhang, Jingjuan; Shan, Fei; Jiang, Duyin (Frontiers in Surgery, 2022)
Burn wounds are dynamic wounds that may present a progressive expansion of necrosis into the initially viable zone of stasis within a short time postburn. Therefore, how to salvage of this zone is of cardinal importance in prevention and treatment strategies of burn wound progressive deepening. This review focuses on the cellular basis of tissue injury and the current progress of prevention and treatment strategies of burn wound progressive deepening, in order to provide references for the treatment of burn wounds in the early phase.